Fibrinogen to albumin ratio as a powerful predictor of the exaggerated morning blood pressure surge in newly diagnosed treatment-naive hypertensive patients - Mahmut Özdemir; Mustafa Yurtdaş; Ramazan Asoğlu; Tarik Yildirim; Nesim Aladağ; Emin Asoğlu (Clinical and Experimental Hypertension, 2020)
Background The exaggerated morning blood pressure surge (MS) is a risk factor for cardiovascular diseases. Inflammation is associated with the pathogenesis of hypertension. We aimed to investigate the association between fibrinogen, albumin, fibrinogen to albumin ratio (FAR), and exaggerated MS, and which of those variables is a better predictor for identifying an exaggerated MS in newly diagnosed treatment-naive hypertensive patients. Material and Methods The study included 249 treatment-naive patients who were newly diagnosed with hypertension in both clinical and ambulatory blood pressure (BP) monitoring measurements. Morning BP was defined as the mean of BPs measured during the first 2 hours after wake-up. The lowest BP was defined as the mean of 3 BP measurements focused on the lowest nighttime computations. The MS was calculated as the morning systolic BP minus the lowest systolic BP. Fibrinogen and albumin levels were measured from venous blood. FAR was obtained by dividing the fibrinogen to the albumin. Results Patients with higher-value MS had a higher fibrinogen, FAR, and a lower albumin than those with low-value MS. MS was positively correlated with fibrinogen and FAR, and negatively correlated with albumin (for all, p < .001). Fibrinogen, albumin, and FAR were independent predictors of exaggerated MS. FAR was a more powerful predictor than fibrinogen (p < .001) and albumin (p = .02) in determining exaggerated MS. Conclusion Patients with exaggerated MS had a higher fibrinogen and FAR, and a lower albumin level than those without exaggerated MS. FAR may be a better predictor than fibrinogen and albumin for determining exaggerated MS.